2000
DOI: 10.3171/jns.2000.93.supplement_3.0177
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience in the treatment of choroidal melanoma with gamma knife radiosurgery

Abstract: Object. The authors report their early results from an ongoing experience treating patients with choroidal melanoma by using gamma knife radiosurgery (GKS). Methods. Between September 1998 and March 2000, 11 patients were treated for choroidal melanoma. Treatment was facilitated with specialized frame placement. Eye immobilization was accomplished with supra- and infraorbital nerve block and tethering sutures to the periorbital tissue. Magnetic resonance imaging was performed to localize the tumor for treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Langmann et al have reported the lowest doses of definitive single fraction radiosurgery for the treatment of ocular melanoma (29). Using a mixture of dose regimens ranging (32,33). The high control rates and minimal radiation related complication rates in these two series are likely related to the relatively short follow-up periods of less than 14 months.…”
Section: Discussionmentioning
confidence: 91%
“…Langmann et al have reported the lowest doses of definitive single fraction radiosurgery for the treatment of ocular melanoma (29). Using a mixture of dose regimens ranging (32,33). The high control rates and minimal radiation related complication rates in these two series are likely related to the relatively short follow-up periods of less than 14 months.…”
Section: Discussionmentioning
confidence: 91%
“…Previous retrospective series, in which the outcomes of GKS in the treatment of uveal melanoma were evaluated, have shown mixed results. 4,7,15,16,19,21,24,28,29 Modorati et al 18 reported that the 3-year probability of survival for uveal melanoma after GKS was 88.8% and the 5-year probability of survival was 81.9%. Fakiris et al 9 showed that the 3-and 5-year overall survival rates were 86% and 55%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A report from the Journal of Neuroscience in 2000 described this technique of immobilization in which patients were required to have local nerve block in the form of injectable anesthetic applied before tethering sutures were inserted to keep the eye fixed during treatment. While not a limitation for the use of GKS, it is important to note that the authors also used a 40-Gy dose prescribed to the 50% isodose line, as compared to our study, which used a lower dose, 30 Gy, to a median 74% isodose line [20]. When considering enucleation versus radiation therapy for treatment, it is important to mention the Cooperative Melanoma Study (COMS), which demonstrated similar 5-year survival rates for both scleral plaques (82%) and enucleation (81%) [21].…”
Section: Discussionmentioning
confidence: 95%